2012
DOI: 10.3892/ol.2012.999
|View full text |Cite
|
Sign up to set email alerts
|

Functional variants at the miRNA binding sites of the E2F1 gene and its mRNA expression

Abstract: Abstract. The transcription factor E2F1 is a key regulator of cell proliferation and apoptosis, and deregulated expression of E2F1 has been frequently found in a number of malignancies. Previous studies have indentified that E2F1 genetic 3' untranslated region (3'UTR) microRNA (miRNA) binding site variants are significantly associated with cancer risk; however, the roles of genetic variants in the E2F1 3'UTR in its post-transcriptional regulation have not been elucidated. Hence, using mRNA expression data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…involved in non-small cell lung cancer, Chronic myeloid leukemia, Cell cycle pathways. E2F1 have MicroRNAs (miRNAs) binding site which is illustrated to have significant association with cancer (Katz et al (2015); Zhao et al (2013)). Mutations in BRCA1 and BRCA2 is experimentally implicated in OC Sowter and Ashworth (2005).…”
Section: Discussionmentioning
confidence: 99%
“…involved in non-small cell lung cancer, Chronic myeloid leukemia, Cell cycle pathways. E2F1 have MicroRNAs (miRNAs) binding site which is illustrated to have significant association with cancer (Katz et al (2015); Zhao et al (2013)). Mutations in BRCA1 and BRCA2 is experimentally implicated in OC Sowter and Ashworth (2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, very weak evidence of an association with a decreased risk of orofacial clefts was demonstrated for the 3′ untranslated regions SNP in E2F1 . This transversion (rs3213180) located in the putative microRNA (miRNA) binding site was found to be significantly correlated with the expression of E2F1 in lymphoblastoid cell lines (Zhao et al, ). Of interest, multiple‐SNP analysis revealed that the haplotype composed of E2F1 rs3213180 and rs2071054 is a protective factor against NSCL/P and this result remained statistically significant even after the permutation‐based correction.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs inhibit gene expression mainly by interacting with a specific site in the 3'-UTR of target mRNA (9). Several studies have demonstrated that miRNAs are involved in various biological functions, including tumorigenesis (10,11).…”
Section: Discussionmentioning
confidence: 99%